2005
DOI: 10.1507/endocrj.52.103
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Infusion Testing in the Diagnosis of Cushing's Syndrome

Abstract: Abstract. Cushing's syndrome and its various aetiologies is a markedly difficult diagnosis to make given its subtle signs, sometime cyclical nature, and the lack of a single definitive diagnostic test. Although a great variety of diagnostic tests have been developed to assist in the diagnosis, even with the best clinical acumen, biochemistry and medical imaging the diagnosis can remain elusive. The long low and high dose oral dexamethasone suppression test is cumbersome, costly and often requiring an extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Thus, by avoiding the intestinal absorption and liver passage, intravenous dexamethasone may be a useful and more consistent alternative. However, this test has not been routinely used and it was previously reported only for differential diagnosis of Cushing’s syndrome using higher doses of dexamethasone [13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, by avoiding the intestinal absorption and liver passage, intravenous dexamethasone may be a useful and more consistent alternative. However, this test has not been routinely used and it was previously reported only for differential diagnosis of Cushing’s syndrome using higher doses of dexamethasone [13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Abou Samra et al 11 reported that Day 2 cortisol was >276 nmol/l in 10 patients with CS and <83 nmol/l in 21 normal subjects. Tran et al 12 reported Day 2 cortisol of ‡350 nmol/l in 11 patients with CS. Furthermore, Abou Samra et al 11 used a competitive protein-binding method for the estimation of cortisol, which is less specific compared to modern immunoassays.…”
Section: Discussionmentioning
confidence: 46%
“…11,12 We have also quantified the response in overweight/obese subjects with type 2 diabetes. These results are consistent with two previous studies demonstrating a sustained suppression of the HPA axis in normal subjects using the same IVDST protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations